Wide‐area smart grids with new smart units synchronized measurement analysis and control based on cloud computing platform. (8th September 2015) - Zhao, Jianyang; Ding, Weihong; Zhan, Lingwei; Shao, Heshuai; Sun, Chengfu; Liu, Yilu
Summary: The problems of energy shortage engage us to find new resource, and varieties of renewable energy produced in different places are looking forward to be feedback to the power grids. These requirements also make power grids start to change from centralized structure with a few power plant to distributed system with many generating stations. To fit the building requirement of Smart Grid, smart units and their information networks with functions of measurement protection and control are becoming necessities. This paper tries to give a new small grid with curtains applications. Around this grid needs, paper introduces the development of Smart Units, the real‐time networks and information web services: (i) The Smart Unit is multi‐μPU instruments with function of measurement analysis and control, which includes intelligent algorithms of FFT Zoom‐FFT Wavelet to fit signal processing, networks communication protocols with Ethernet and 3G/4G interfaces, and controlling functions to control devices like Intelligent Broker and Intelligent Capacitor; (ii) Based on Ethernet, a real‐time controlling protocol named Synchronous Ticket Strategy (STS) is proposed, which is used to manage to synchronize measurement and control; and (iii) Information web services are built on cloud computing platforms, which provide parallel calculation with S transmit and user application services like power parameters GIS and data accessing. At the end some results are given from simulations of algorithms and online tests. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper gives a new smart grid with Smart Units, the real‐time networks and information web services. The Smart Units with functions of measurement analysis and control include intelligent algorithms of FFT Zoom‐FFT Wavelet. The networks working in Synchronous Ticket Strategy are a real‐time controlling system. Information web services built on cloud computing platforms provide parallel calculation with S transmit and user application services of power parameters GIS and data accessing.